New Lignans from the Leaves and Stems of Kadsura philippinensis - Chang-Hung Chou; Yao-Haur Kuo; Michael Y. Chiang; I-Wen Lo; Chia-Ching Liaw; Yuan-Bin Cheng; Yu-Chi Lin; Ya-Ching Shen (Molecules, 2013)
Three novel C19 homolignans, taiwankadsurins D (1), E (2) and F (4), and two new C18 lignans kadsuphilins N (3) and O (5) were isolated from the aerial parts of Taiwanese medicinal plant Kadsura philippinensis. The structures of compounds 1–5 were determined by spectroscopic analyses, especially 2D NMR techniques. The structure of compound 5 was further confirmed by X-ray crystallographic analysis. Compounds 1 and 2 have a 3,4-{1'-[(Z)-2''-methoxy-2''-oxoethylidene]}-pentano(2,3-dihydrobenzo[b]furano)-3-(2'''-methoxycarbonyl-2'''-hydroxy-2''',3'-epoxide) skeleton.